Kinerja Organisasi Pusat Pelatihan Olahraga Pelajar (PPOP) DKI Jakarta Dalam Meningkatkan Prestasi Atlet Sepakbola - Rido Rizki Andriawan; Nida Handayani (Jurnal Media Administrasi, 2024)
The DKI Jakarta Student Sports Training Center (PPOP) is an organization that operates in the field of student sports training in DKI Jakarta Province, one of which is football. The DKI Jakarta PPOP football team experienced two consecutive defeats in official competitions in the 2022 Soeratin Cup U-17 and 2023 Porseni NU championships. The aim of the research is to look at the performance of the DKI Jakarta Student Sports Training Center using organizational performance theory. The method used is descriptive with a qualitative approach. The research results show that the productivity indicators are good, this can be seen from the success in achieving the predetermined targets. In terms of service quality indicators, it has provided quite complete facilities with quality facilities and infrastructure which are also in very good condition, however the quality of the grass on the field at PPOP DKI Jakarta is different from that used on official match fields, so this is a problem. problems that arise for football athletes. In terms of responsiveness indicators, it is good, this can be seen from the fact that all staff at PPOP DKI Jakarta can carry out their duties well, are friendly and also informative to all people who need services. The responsibility indicators are quite good. This can be seen through the actions taken in creating work plans and programs required by football coaches and athletes. Apart from that, monitoring is also carried out on programs that have been prepared and implemented to see existing developments. The accountability indicator has been implemented well, this can be seen in the preparation of the annual work plan and the finances are explained in detail to the relevant stakeholders.